NUH ALAYHISSALOM QISSALARIDA JАNRLАR RАNG-BАRАNGLIGI - Qo‘ldoshevna , Mamatova Sadbara; Qo‘ldoshevna , Mamatovadbara (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The narratives of prophets, particularly those of Nuh (Noah) Alayhissalam, are central to Islamic religious texts and hold significant cultural and theological value. These accounts are not only integral to Islamic tradition but also offer insights into the evolution of religious storytelling. Within the genre of prophetic narratives, the stories of Nuh Alayhissalam present a unique interplay of thematic elements and narrative structures. These stories span various dimensions of human experience, divine intervention, and moral instruction, revealing diverse literary techniques and symbolic representations. Despite the rich tapestry of these narratives, there is a lack of comprehensive scholarly analysis that explores the range and significance of literary devices employed across different texts and traditions. Existing studies often focus on isolated elements rather than providing a cohesive understanding of the narrative's genre and its broader implications. This study aims to analyze the narrative diversity within the stories of Nuh Alayhissalam, examining the various genres and thematic elements present in these accounts. The objective is to identify and articulate the literary and symbolic variations and their implications for religious and cultural interpretations. Preliminary findings indicate a significant variance in narrative techniques and symbolic content across different sources, reflecting a complex interplay of cultural, theological, and literary factors. These variations offer new insights into how these stories function within their respective traditions. This research contributes a novel perspective by systematically categorizing the genre and narrative strategies of Nuh Alayhissalam's stories, bridging gaps between textual analysis and theological interpretation. The study’s findings provide a deeper understanding of the narrative complexity within prophetic stories, enhancing scholarly discourse and offering valuable perspectives for both religious studies and comparative literature.